Pengaruh Penggunaan E-commerce terhadap Peningkatan Pendapatan Usaha Mikro Kecil Menengah (Penelitian di Kota Palembang): Pengaruh Penggunaan E-commerce terhadap Peningkatan Pendapatan Usaha Mikro Kecil Menengah (Penelitian di Kota Palembang) - Ambarwati, Silvy; Putri Achira, Shabrida; Cahyaazwari, Peny (Jurnal Ekonomi KIAT, 2023)
The purpose of this research is determine the influence of E-commerce on MSME income in Palembang. The research method applied in this research is quantitative methods, using primary data which was obtained through distributing questionnaires using google form to MSME in Palembang.This research uses PLS analysis with the help of SmartPLS 3.0 software. The results of this research indicate that the E-commerce have a positive and significant effect on MSME income in Palembang. This is proven by the coefficient of determination in the sufficient category with an R2 value of 0,600 or 60%.